Design and application of a lightweight management software for Internet of things node - Shiyou GUAN; Zaiqun WU (物联网学报)
The modular design idea was used to abstract the logic of IoT nodes, and the function and control logic of nodes were divided into atoms, the atomic modules can be freely combined and deployed according to different application, they support single system and distributed system deployment, and were pluggable and easy to expand, meet the diversified design needs of IoT applications.The design and implementation of lightweight IoT node management software based on this idea were described in detail.The test results show that the software only needs 14 872 byte of flash and 1 976 byte of RAM, which can be used in limited hardware resources.This software framework was used to design smart hotel RCU(room control unit), including the design of voice gateway node based on esp32 (Wi-Fi SOC) and 4-bit key panel node based on cx32l003 (MCU).The RCU designed with this software framework can deploy to different hotels only needed to be designed once, which solves the problem that RCU cannot be used in different hotels and needs to be designed and modified repeatedly, and greatly speeds up the process of smart hotel deployment.At present, the RCU has been deployed and operated stably in Xi'an, Tupai and other express hotels.